Experimental Analysis of the Influence of Wushu Teaching on Male College Students in China - WenWang; Tonggang Fan, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The decline of college students' physical fitness in China has always been one of the major problems plaguing China's education, in general and physical education, in particular. This decline is attributed to the inadequacy of physical education (PE) in colleges. Wushu as a kind of martial arts is an important course of college PE in China, attracting lots of male college students. However, the routine teaching of traditional Wushu courses lacks exercises, failing to enhance the physical health of students. To reform the teaching methods of Wushu, this paper proposes an innovative Wushu teaching method under the Chinese Health Sports Course Mode (CHSCM to simplify the routine teaching of Wushu and emphasize on strengthening physical fitness and arranging lots of exercises without exhausting the students and improving their physical fitness. In this direction, a 12-week experiment was carried out to compare the effects of the proposed innovative teaching method with the traditional teaching method of Wushu. The results show that: (1) the male college students trained by the innovative method achieved much better body shape, physical function, and physical fitness than those trained by the traditional method, because the latter method does not offer enough exercise volume or classroom training; (2) despite being inferior to the innovative method, the traditional method significantly improved the flexibility in physical fitness; (3) Wushu teaching should combine flexibility and muscle strength, and maintain certain exercise intensity and duration.